Examining the Relationships Between Job Characteristics and Employees' Job Satisfaction in the Fisheries Development Authority of Malaysia - Mohd. Khir, Mohd. Sham (2004)
The main purpose of this study is to examine the relationships between the job characteristics and the level of employees’ job satisfaction in the Fisheries Development Authority of Malaysia (FDAM). The data was collected from 150 respondents by using a structured questionnaire. The data was analyzed by using Pearson Correlation, T-Test and ANOVA. Results of the study indicate significance relationships between job characteristics and job satisfaction. As a whole, the findings of the study can be summarized as follows :